IMPLEMENTATION OF THE ENVIRONMENTAL CARE AND CULTURE MOVEMENT IN SCHOOLS - Muh Khamid; Setya Raharja; Aqsal Rizky Ramadhan; Ridwan Eko Apriyanto; Khatibul Umam Salam (Jurnal Eduscience)
Purpose–This research aims to describe the implementation of the Environmental Care and Culture Movement in Schools at the National Adiwiyata School